Enhancing accountability and effectiveness of foreign aid - Nepal, Ram Babu (1998)
Foreign aid plays significant role in accelerating development in countries like ours. In recent decades, donors (both bilateral and multilateral) and recipients are facing the critical challenge of enhancing effectiveness of aid, that is, ensuring their financiers and stockholders that aid is pursuing intended objectives. They are constantly asked by stakeholders for relevant and reliable information that justifies the effectiveness of aid, promotes accountability and transparency. Accountability is the heart of governance and has to do with holding officials responsible to their actions. It is the obligation of persons or entities, including public enterprises and corporations, entrusted with public resources to be answerable for the fiscal, managerial and programme responsibilities that have been conferred on them, and to those that have conferred these responsibilities on them. Effectiveness is not a single indivisible concept. It contains subjective, value-laden components that will normally change with time and viewpoint. It is the result of performance and understood as the capability of achieving intended objectives. The effectiveness of an activity is the extent to which the actual outcome of the activity matches with the objectives of that activity. Where there are unintended negative effects from the activity, effectiveness must be judged on the basis of the net balance of positive and negative outcomes. Various factors contribute in enhancing accountability and effectiveness of aid. However, the most significant factors are: effective financial management and control system, clear articulation of accountability relationships, clear and precise performance measures, indicators and reporting systems, and auditing. Nepal faces several interrelated problems in ensuring effectiveness and enhancing accountability. Some of the major problems are related to measurement of effectiveness, financial management and control systems. Contribution of foreign aid to the socio-economic development of Nepal is immense. Improvement in the management of aid to enhance its effectiveness is the matter of concern both to recipients and donors. Hence, it is very essential to identify measures that contribute towards promoting accountability relationships, effectiveness, quality of information and performance reporting. The role of audit needs to be reasonably appreciated both by donors and governments to obtain objective and reliable information on the real benefits of aid and other prominent issues that have broad implications on the national economy. Similarly, we need to review ways and means that were initiated earlier, to evaluate their strengths and weaknesses before introducing new measures. - Reproduced
Keywords: Accountability - Nepal; Foreign aid - Nepal; Foreign aid